Organization New Forms: Old Strategies during the E-Strategies Studying in the Cultural Industry - et. al., Rajkumar Sharma , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The internet cultural era has shown a high interest for scientists and experts in the use of web (Internet, Intranet and Extranet) resources in electronically helping companies and organizations (e-operation) (ICE). However, while network technology is of great importance and high expectations for companies, the use of network technology by these internet-based organizations and the strategies these companies formulate and deploy for competing in ICE remain unclear. This paper examines the adoption of network technology among 56 Small to Medium-sized Enterprises (SMEs) in the logistics and tourism sector. It focuses on how these SMEs are unlearning their old strategy formulation and implementation and are engaging in e-strategy formulation. Reported findings indicate considerable gaps between theory and practice. The article indicates that SMEs are required to examine a number of situational antecedents to recognize e-strategic opportunities in order to leverage the network technology to its full potential. The work, thus, provided a fresh insight into the existing approaches for evolving types of organizations, and as such, scholars and practitioners alike are likely to be involved.